Sacroiliitis during isotretinoin treatment: Causal association or coincidence? - Aydog, Ece (North Clin Istanb, 2018)
Isotretinoin, a retinoid derivate used in acne treatment, has a variety of side effects involving the musculoskeletal system; however, sacroiliitis is rarely observed. Our aim was to present nine cases of sacroiliitis in patients being treated with isotretinoin. Sacroiliitis was identified and monitored using magnetic resonance imaging (MRI). Clinical symptoms were resolved with nonsteroidal anti-inflammatory drug therapy after isotretinoin treatment was ceased. Different from the other cases, follow-up MRI was done. Follow-up MRI revealed improvement in some patients. Although the association between isotretinoin therapy and sacroiliitis has been covered in literature, this association is not yet completely understood. We aimed to discuss the relationship between two.